Enough to Feed Ourselves!—Food Plants in Bulgarian Rural Home Gardens - Teodora Ivanova (MDPI AG, 2021)
The home garden is a unique human-nature interspace that accommodates a diverse spectrum of plant species and provides multiple services to households. One of the most important roles of home gardens is to shelter the agricultural plant diversity that provides for diverse and healthy nutrition, especially in rural communities. While tropical home gardens have received wide recognition due to their provisional function for the local communities, temperate and especially European home gardens have been discussed less frequently as a source of subsistence. The main objectives of the current study were to document plant species grown in Bulgarian rural home gardens and to explore related local knowledge and cultural practices that influence food plant diversity, its selection and preservation. Field work was focused on settlements situated in eight provinces in South and North-West Bulgaria. Participants representing 65 home gardens were approached through semi-structured interviews. Home gardens were found to harbor 145 cultivated and semi-cultivated plant taxa, used as food, medicinal and aromatic plants and as animal fodder. Members of the Rosaceae family were most numerous. The largest part of the garden area was occupied by vegetable crops of Solanaceae and Cucurbitaceae. In 63.1% of the studied households, the food growing area comprised more than 2/3 of the total size of the garden. Most preferred crops reflected the social and cultural importance of food self-provisioning, especially in the rural areas. The provisional role of the home gardens in regard to preparation of traditional foods and the driving forces for seed saving are discussed.